Analysis of the Understanding, Experience/Appreciation, and Satisfaction Levels of the Faithful Regarding the Dialogue between the Church and Culture in the Diocese of Maumere - Yanuarius Hilarius Role; Maximus Manu; Markus Anggelico Doni Lewar Anggelico Doni Lewar; Kostodia Pito (Jurnal Ledalero, 2025)
The Diocese of Maumere, like other Catholic dioceses in Indonesia, serves as a center for both spiritual and social activities for Catholics in the Sikka Regency. In practice, however, the life of the faithful in this diocese is not without tension between local culture and religious teachings. For instance, dualistic practices still exist in how religion and culture are understood. When praying for the salvation of ancestral souls, for example, the prayer is often followed by the ritual of “Tung Piong,” whether performed after Mass in church or at home. This research aims to analyze the level of understanding, appreciation, and satisfaction of the faithful regarding the dialogue between the Church and culture in the Diocese of Maumere. By gaining insights into these areas, the Church can develop programs and policies that are better aligned with the needs and expectations of the faithful, enhancing its effectiveness in fulfilling its spiritual and social responsibilities. Additionally, this research helps the Church evaluate the effectiveness of its current approach to engaging with local culture. It encourages the Church to adopt more inclusive and participatory strategies, ensuring that all congregation members feel valued and actively involved in the dialogue process. The method used in this study is a quantitative survey analysis, with respondents representing a range of age groups, genders, educational levels, and occupational backgrounds. This study reveals a strong relationship between the three research variables: understanding, appreciation, and satisfaction in the dialogue between religion and culture. Greater understanding leads to increased appreciation, which in turn results in higher satisfaction. Therefore, it is recommended that ongoing research and continuous efforts to raise awareness about religious teachings and the noble cultural values that should be preserved and practiced remain essential for fostering a deeper faith.